The role of computed tomography in diagnosing an acute abdominal pain in ileocecal area - Spirov, Goran; Spirov, Vasilcho; Stojovska Jovanovska, Elizabeta (Balkan Society of Radiology, 2017)
Purpose: To evaluate the role of computed tomography (CT) in diagnosing acute abdominal pain in ileocecal area. Materials and Methods: Retrospectively 457 CT reports of abdomen and the complementary clinical records of patients over the age of 16 presented between April 2016 and June 2016 were reviewed. Considered inclusive criteria were: acute abdominal pain in ileocecal area and negative or inconclusive physical examination, laboratory tests and abdominal ultrasound. Patients with known abdominal disease or previous surgery were omitted. In all patients the abdomen was scanned with 16-row multidetector CT with 2.5mm collimated slice width from dome of diaphragm to pubis symphysis. Intravenous contrast media was administrated if no signs of appendicitis were found. The surgical or clinical record was used for follow-up. Results: Only 33 patients fulfilled the criteria to be included in the study. Radiological diagnosis was reached in 30 of 33 patients (91%). Most common reported entity was appendicitis (33%), followed by infiltrative lesion of colon (30%) and nonspecific inflammatory disease of terminal ileum and cecum (12%). Diverticulitis, epiploic appendicitis and ectopic pregnancy were reported in 5 cases (15%). Out of 33 patients 3 (9%) had nonspecific radiological findings. Surgery was performed in 23 patients (70%). Operative report matched radiological findings in 22 cases (96%). Conclusion: CT is a method of choice for improving accuracy in diagnosing acute abdominal pain in ileocecal area.